Development of power qualities of skilled water-polo players - Ostrovsky M.V; Chaplinsky M.M; Polehoyko M.B; Maksymova N.V; Dunec-Lesko A.V (Kharkov National Pedagogical University, 2010)
In the training process of water-polo players basic attention of trainers is concentrated on the technical tactical actions of players. Development of physical qualities of water-polo players carried out unsystematic. The purpose of work is an improvement of method of power preparation of skilled water-polo players. In experiment took part 26 skilled water-polo players (MS -14 and KMS - 12) in age from 21 to 32 years. The complex of experimentally confirmed exercises is presented for development of power qualities of skilled water-polo players. Purposeful development of power possibilities of water-polo players accompanied reliable (р≤0,05) high growth of power qualities rates.